The uses of hematopoietic stem cell transplantation to restore the production of blood cells in cancer treatment - Abu Hashim, Nur Athirah; Wan Zawawi, Wan Nursyahirah; Othman, Siti Amira; Mohammed, Elizah (Penerbit UTHM, 2022)
Hematopoietic stem cells (HSCs) are a limited group of all blood cell types. A study was performed on the spleen of mice undergoing bone marrow transplantation to determine the potential colonization of red blood cells. This bone marrow transplant has been leading in treating malignant diseases. High-dose chemotherapy with hematopoietic stem cells has been commonly used in the diagnosis of haematologic allegiances. This is a clinical trial of autologous and allogeneic transplants which takes the latest developments in blood progenitor cells into consideration. Prior to transplantation, patients underwent intensive myeloablative chemotherapy with a "rescue" stem cell. Autologous HSCT was performed using hematopoietic stem cells of the patient's own, pre-transplantation removed and after myeloablation reinjected. This century has produced a range of approaches and innovations that have been used including modern mobilization approaches and the invivo production of blood progenitor cells, the use of core cord blood as alternative cell source, and molecular techniques that could include other forms of purifying tumor cells from potential autologous lists.